I survived true stories : five epic disasters - Tarshis, Lauren (New York : Scholastic Press, 2014)
Presents five true stories of survival, featuring real kids in the midst of disasters, from a group of students surviving the 9.0 earthquake that set off a historic tsunami in Japan, to a boy nearly frozen on the prairie in 1888, these kids lived to tell tales of unimaginable destruction.
Children's blizzard, 1888 -- Titanic disaster, 1912 -- Great Boston molasses flood, 1919 -- Japanese tsunami, 2011 -- Henryville tornado, 2012.
Includes bibliographical references.
6.0
3-6
930L
S
Keywords: Natural disasters -- Juvenile literature; Disasters -- Juvenile literature; Survival -- Juvenile literature; Natural disasters; Disasters; Survival; Natural disasters; Survival after airplane accidents, shipwrecks, etc